Précarité économique, instabilité de l’emploi et pratiques sociales en Syrie - Thierry Boissière (Revue des Mondes Musulmans et de la Méditerranée)
In the past twenty years, Syria has experienced periods of growth alternating with periods of economic instability, followed by a weakening of the welfare State and attempts at economic liberalisation and labour market segmentation; as a result, an increasing number of people have suffered from the deterioration of working conditions. This study begins with an analysis of social and economic practices used to cope with these difficulties by two categories of workers: state employees and wage workers in the private sector. Next, it focuses on some patterns of resource mobilisation that have recently developed in the Syrian society.